Pursuing the mission of third sector organizations in the context of interorganizational networks: implications to strategy - Simaens, A. (European Academy of Management Conference, EURAM 2019, 2019)
Third Sector Organizations (TSOs) face multiple sources of complexity in the pursuit of their missions. These include the institutional, problem, strategic, and operational complexities explored in this paper. There are increasing demands on TSOs to fill the gaps in social provision arising as sections of society face ever more difficult economic and financial conditions. However, the TSOs themselves are also faced with growing challenges, particularly in terms of access to resources. Funding sources have less available to disperse due to the demands of austerity, and the competition among TSOs for that diminishing pool of resources is increasing. The increasing complexity faced by TSOs has demanded new forms of cooperation and interorganizational coordination. It is in the context of multiple networks of relationships, both serendipitous and goal-directed, that this paper explores a systems approach to mission pursuit. Based on an empirical study with twenty-three TSOs belonging to an interorganizational network, we explore not only the environmental interconnectedness and complexity they face, but also the role of interorganizational relationships within the boundaries of the network for mission pursuit. The findings suggest that these TSOs face multiple enablers and barriers in the pursuit of their missions, related to a set of interorganizational relationships both within and outside the borders of the goal-directed network. The mechanisms of competition and cooperation detected are also explored.